Faktor Pemasaran Dalam Pengelolaan UMKM di Tengah Pandemi Covid-19 - Citra Eliyani; Syamruddin Syamruddin; Ivan Putranto (Jurnal Madani: Ilmu Pengetahuan, Teknologi, dan Humaniora, 2021)
This research aims to find out the development of UMKM in South Tangerang City, and to find out marketing factors in the management of UMKM in South Tangerang City during the Covid-19 pandemic. This research method is qualitative. The research was conducted on UMKM in South Tangerang City. Determination of informants as selected data sources using purposive sampling techniques. Data collection uses observation, interview and documentation techniques. The validity of data is obtained through credibility, transferability, dependability, and confirmatory. Qualitative data analysis: data reduction, data exposure, and conclusion withdrawal. The results showed that: 1) The number of UMKM in South Tangerang City in 2020 amounted to 90,128, with details: Pamulang District as many as 17,919, Ciputat District as many as 13,508, East Ciputat District as many as 12,838, Pondok Aren District as many as 17,944, Serpong District as many as 12,607, North Serpong District as many as 9,511, and Setu District as many as 5,801. UMKMs are divided into various types: accommodation, accessories, expeditions, electronics, pharmaceuticals, fashion, furniture, other services, hp counters, creative, culinary, automotive, care/ health, fisheries, agriculture, vegetables / fruit, grocery stores, and transportation. 2) Marketing carried out by UMKM in South Tangerang City during the Covid-19 pandemic is: in terms of products, in addition to new product offerings, innovations are also made to existing products so that they are more attractive to consumers; in terms of price, many UMKM managers make adjustments; in terms of promotion, in addition to the provision of discounts, promotions are done by word of mouth, networking the UMKM community as well as online; From the side of the place, from the side of the place, the sales system carried out during the Covid-19 Pandemic is more limited, UMKM managers use more means through the online system. Concluded that in the face of the Covid-19 pandemic, it is necessary to use appropriate marketing strategies, one of which is through online media. Abstrak Penelitian ini bertujuan untuk mengetahui perkembangan UMKM di Kota Tangerang Selatan, dan untuk mengetahui faktor pemasaran dalam pengelolaan UMKM di Kota Tangerang Selatan selama masa pandemi Covid-19. Metode penelitian ini adalah kualitatif. Penelitian dilakukan terhadap pelaku UMKM di Kota Tangerang Selatan. Penetapan informan sebagai sumber data yang dipilih menggunakan teknik purposive sampling. Pengumpulan data menggunakan teknik observasi, wawancara dan dokumentasi. Keabsahan data diperoleh melalui credibility, transferability, dependability, dan confirmatory. Analisis data kualitatif: reduksi data, paparan data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: 1) Jumlah UMKM di Kota Tangerang Selatan pada tahun 2020 berjumlah 90.128, dengan rincian: Kecamatan Pamulang sebanyak 17.919, Kecamatan Ciputat sebanyak 13.508, Kecamatan Ciputat Timur sebanyak 12.838, Kecamatan Pondok Aren sebanyak 17.944, Kecamatan Serpong sebanyak 12.607, Kecamatan Serpong Utara sebanyak 9.511, dan Kecamatan Setu sebanyak 5.801. UMKM tersbut terbagi ke dalam berbagai jenis: akomodasi, aksesoris, ekspedisi, elektronik, farmasi, fashion, furniture, jasa lainnya, konter hp, kreatif, kuliner, otomotif, perawatan/kesehatan, perikanan, pertanian, sayuran/buah, toko sembako, dan transportasi. 2) Pemasaran yang dilakukan oleh UMKM di Kota Tangerang Selatan selama masa pandemi Covid-19 yaitu: dari sisi produk, selain penawaran produk baru, dilakukan pula inovasi terhadap produk yang sudah ada sehingga lebih menarik konsumen; dari sisi harga, banyak pengelola UMKM yang melakukan penyesuaian; dari sisi promosi, selain pemberian diskon, promosi dilakukan melalui mulut ke mulut, networking komunitas UMKM serta secara online; dari sisi tempat, dari sisi tempat, sistem penjualan yang dilakukan selama Pandemi Covid-19 lebih bersifat terbatas, pengelola UMKM lebih banyak menggunakan sarana melalui sistem online. Simpulan bahwa dalam menghadapi pandemi Covid-19 seperti saat ini maka perlu digunakan strategi pemasaran yag tepat, salah satunya melalui media online. Kata Kunci: Covid-19, Pemasaran, Pengelolaan UMKM